Oil and Gas Enterprise, Effect of Compensation, Working Environment, and Motivation to Performance Account Representative Tax Service Office - HD Simbolon, Linda; Halim, Paisal; Badruddin, Syamsiah; Hendarso, Panji; ., Yulianto; ., Mahfud; Ikhsan Setiawan, Muhammad; Saleh A, A (International Journal of Engineering and Technology, 2018)
According to Gibson et al. (2012) quoted by Wibowo (2015) "Performance is the result of work related to organizational objectives such as quality, efficiency and other criteria of effectiveness." Account Representative Performance is a result of the Account Representative in performing his duties in accordance with the responsibilities assigned to him. Compensation, work environment, and motivation is Believed Account Representative will effect performance. According to some experts, compensation effect on performance (Holt, 1993) and compensation Becomes the main thing to Attract and MOTIVATE employees to improve Reviews their performances (Ivanceikh and Glueck, 1989); work environment effects on performance (Leaman, 1995); effects on performance and motivation (Vroom, 1964; Moorhead and Griffin, 1998). The purpose of this study is to analyze the effect of compensation, work environment, and motivation on Account Representative Performance of Oil and Gas Tax Office. This research was conducted by taking the samples from all Account Representatives of Oil and Gas Tax Office as many as 37 respondents. Data were collected through questionnaires in the form of a list of statements. The technique of data analysis used is Multiple Linear Regression Analysis using SPSS Version 23. Based on the result of the analysis, it was proved that compensation, work environment and motivation have a positive and significant influence on Account Representative performance of Oil and Gas Tax Office either partially or simultaneously.Â Â